2022
DOI: 10.4314/gjl.v11i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Different pronouns, same referents

Abstract: In recent times, studies on I, we and you (tri-PP) in academic lectures havefocused on the L1 context. This paper, however, investigates thecommonalities in the discourse reference of I, we, and you across threedisciplinary supercommunities (DSs): Humanities (HS), Social Sciences(HS), and Natural Sciences (NS), using a corpus from an L2 context. Theconcordance tool in AntConc was used to search for all instances of the tri-PP. The referents of the tri-PP were identified based on the contextual andco-textual cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Inclusive "we" is used to refer to both the speaker and audience (Kaewrungruang & Yaoharee, 2018). Akoto & Afful (2022) alluded to the traditional semantic mappings "I + you" as inclusive "we", and "I + they" as exclusive "we". The following are some examples of the inclusive "we".…”
Section: The Use Of Inclusive "We" "Our" and Us"mentioning
confidence: 99%
“…Inclusive "we" is used to refer to both the speaker and audience (Kaewrungruang & Yaoharee, 2018). Akoto & Afful (2022) alluded to the traditional semantic mappings "I + you" as inclusive "we", and "I + they" as exclusive "we". The following are some examples of the inclusive "we".…”
Section: The Use Of Inclusive "We" "Our" and Us"mentioning
confidence: 99%
“…This supports the idea of inter-personal shift, in which a speaker employs alternative pronouns to identify himself (Gibbons & Macrae, 2018). This is referred to as nosismthe scenario in which the referent of 'we' is a single speaker (Maxey, 2016;Akoto & Afful, 2022). It was found that the linguistic resources of the music utilized the nosism 'we' as a kind used for individuals rather than collective speakers.…”
Section: We For the Addresser (Composer)mentioning
confidence: 99%
“…Grammatically, 'you' is considered addressee-oriented (Akoto & Afful, 2022). Hyland (2009) has also argued that "you" is the clearest way a writer can acknowledge the reader's presence.…”
Section: You-sphere Referentsmentioning
confidence: 99%
See 1 more Smart Citation